PELATIHAN RETORIKA DAN MENULIS TEKS CERAMAH KELAS XI SMK NUSANTARA 02 KESEHATAN (KORELASI MENULIS TEKS CERAMAH DAN PRAKTIK RETORIKA) - Dwi Septiani; Rerin Maulinda; Desi Karolina Saragih; Aryani Aryani (JPM PAMBUDI, 2020)
Writing skills are an important aspect of academic performance as well as performance related to active skills that must be mastered, including in class XI SMK students. However, there are still many students who are not good at it, including writing lecture texts. Apart from the lack of skill in writing lecture texts, advanced stages such as rhetoric practice (lectures) are still low. Thus, this study focuses on examining the correlation between lecture text writing skills and achievement in rhetorical practice (lecture). The method used in this research is descriptive quantitative method with 50 participants of class XI SMK 02 Nusantara Kesehatan who have previously participated in online Community Service (PKM) activities carried out by the Indonesian Literature Study Program at Pamulang University with the theme "Rhetorical Practical Online Training in Writing Skills. Text of the Class XI Student Lecture at SMK Nusantara 02 Kesehatan "which was held 7—1 September 2020 with Google Meet media. The result of this study is a very significant influence between the skill of writing lecture texts (X) on the achievement of rhetoric practice (Y), which is 0.926. In addition, there is a contribution made by the skill of writing lecture texts (X) to the achievement of rhetoric practice (Y), which is 85.8%.